PENGARUH ADAPTABILITAS, PENGGUNAAN SOCIAL MEDIA dan LITERASI KEUANGAN TERHADAP KINERJA PEMASARAN UMKM KOTA SINGKAWANG SEKTOR MAKANAN dan MINUMAN - Ket Cung (Jurnal Akuntansi dan Manajemen Bisnis, 2023)
The Influence of Adaptability, Use of Social Media, and Financial Literacy on the Marketing Performance of UMKM in Singkawang City in the Food and Beverage Sector MSMEs are among the sectors that have been hit the hardest by the COVID-19 outbreak. There were 37,000 MSMEs that reported that they were affected by the COVID-19 outbreak. As many as 56 percent reported a decrease in sales, 22 percent reported problems with the financing aspect, 15 percent reported problems with the distribution of goods, and 4 percent reported difficulties in obtaining raw materials. This study aims to test and analyze the effect of adaptability on the marketing performance of Singkawang City MSMEs in the food and beverage sector; to test and analyze the effect of using social media on the marketing performance of Singkawang City MSMEs in the food and beverage sector; and to test and analyze the effect of financial literacy on Singkawang City MSME marketing performance in the food and beverage sector.his research is a survey based on data collection methods. Based on the type and analysis of the data, this research includes quantitative research. The sources of data used are primary and secondary data. The population in this study were Singkawang City SMEs engaged in the food and beverage sector, with a sample of 75 respondents. The data analysis technique used is multiple linear regression analysis using SPSS 16.0. The results showed that there was no significant influence between adaptability and the marketing performance of Singkawang City MSMEs in the food and beverage sector. The use of social media and financial literacy has a significant influence on the marketing performance of Singkawang City MSMEs in the food and beverage sector.